The Adventures of Sherlock Holmes - Doyle, Arthur Conan, 1859-1930 (London Collins Classics, 2013)
The Adventures of Sherlock Holmes is a collection of twelve stories by Arthur Conan Doyle, featuring his famous detective.
Keywords: Holmes, Sherlock -- Private investigators -- Detective and mystery stories, English